Three‐Dimensional Graphene: A Biocompatible and Biodegradable Scaffold with Enhanced Oxygenation. Issue 10 (4th March 2016) - Loeblein, Manuela; Perry, Guillaume; Tsang, Siu Hon; Xiao, Wenjin; Collard, Dominique; Coquet, Philippe; Sakai, Yasuyuki; Teo, Edwin Hang Tong
Abstract : Owing to its high porosity, specific surface area and three‐dimensional structure, three‐dimensional graphene (3D–C) is a promising scaffold material for tissue engineering, regenerative medicine as well as providing a more biologically relevant platform for living organisms in vivo studies. Recently, its differentiation effects on cells growth and anti‐inflammation properties have also been demonstrated. Here, we report a complete study of 3D–C as a fully adequate scaffold for tissue engineering and systematically analyze its biocompatibility and biodegradation mechanism. The metabolic activities of liver cells (HepG2 hepatocarcinoma cells) on 3D‐C are studied and our findings show that cell growth on 3D–C has high cell viability (> 90%), low lactate production (reduced by 300%) and its porous structure also provides an excellent oxygenation platform. 3D–C is also biodegradable via a 2‐step oxidative biodegradation process by first, disruption of domains and lift off of smaller graphitic particles from the surface of the 3D–C and subsequently, the decomposition of these graphitic flakes. In addition, the speed of the biodegradation can be tuned with pretreatment of O2 plasma. Abstract : Biocompatibility and biodegradation of three‐dimensional graphene (3D‐C ) are studied to investigate if it is an adequate scaffold for tissue engineering. The metabolic activities of liver cells (HepG2) on 3D‐C show that cell growth has high cell viability and higher oxygenation than on other forms of carbon. 3D‐C is also biodegradable via a two‐step oxidative biodegradation process and the speed of the biodegradation can be tuned with pretreatment of oxygen plasma.